PENGARUH LAYANAN ORIENTASI TERHADAP MINAT ENTREPRENEUR SISWA KELAS X SMA NEGERI 4 PEKANBARU TAHUN AJARAN 2015/2016 - Riezty Anggia Novita; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine the effect of service orientation to the interest of the entrepreneur class X SMAN 4 Pekanbaru the academic year 2015/2016. This research was conducted in SMA Negeri 4 Pekanbaru from March 2016 to May 2016. The method used is a method of real-experimental with patterns pretest-posttest control group design. Research subjects in this study were students of class X SMAN 4 Pekanbaru with interest in entrepreneurship rendah.Instrument data collection is questionnaire. Data analysis technique used was the statistical technique korelasi.Berdasarkan Wilcoxon test result turns out there are differences in students 'interest in entrepreneurship before and after the implementation of the service orientasi.Selanjutnya after comparison between the experimental group and the control group by Mann-Whitney test results there are significant differences in the students' interest in entrepreneurship experimental group with interest in entrepreneurship students in the control group. Based on the results of Spearman Rank test the effect of orientation of service to the students' interest in entrepreneurship is 11%.Key words: Services Orientation, Interest Entrepreneur